Agglomeration and clustering of firms in relation to innovation and economic performance (2012)
Agglomeration economies has traditionally been viewed as central to cluster development, in which geographical proximity has facilitated crucial externalities, particularly those relating to generation and diffusion of tacit knowledge through the creation of an innovative environment surrounding the industry. The paper underscores the role of agglomeration and clustering of firms in relation to innovation and economic performance. The paper found out that agglomeration and clustering have tremendous positive effects on regional development. These are economic booster that leads to amazing technological and innovation creation which are driving forces or catalyst for total transformation of social and economic performance of a region. The paper recommends that agglomeration and clustering of firms should be encouraged by government intervention through the provision of infrastructural facilities, credit facilities and implementation of tax holiday.